Effect of sowing density and nitrogen top-dress fertilisation on growth and yield of chia (Salvia hispanica L.) in a Mediterranean environment: first results - Bochicchio, Rocco; Rossi, Roberta; Labella, Rosanna; Bitella, Giovanni; Perniola, Michele; Amato, Mariana (Italian Journal of Agronomy, 2015)
The demand for sources of nutraceuticals has led to the rediscovery and diffusion of traditional crops such as chia (Salvia hispanica L.), whose leaves and fruits are rich in W3 fatty acids and anti-oxidants. Chia originates in Central America but it is rapidly expanding to new areas. A field experiment conducted at Atella in Basilicata (Southern Italy) was set up to test the response of chia to N top-dress fertilisation (0 and 20 kg ha–1) and to sowing density (D1=125, D2=25, D3=8 and D4=4 plants m–2) in a split-plot design with three replications. First results show maximum leaf area index values up to 7.1 and fresh vegetative biomass production at early flowering ranging between 50.87 (D4) and 59.71 (D1) t ha–1. Yield increased with plant density: a significantly (P<0.01) higher production (398 kg ha–1) was reached in D1. N top-dressing had a detrimental effect on yield and corresponded to higher lodging and lower maturation percentage of seeds, though non-significant. Based on our first results it seems worthwhile to continue agronomical trials for chia in herbaceous systems of southern Italy for leaf production based on traditional genotypes, while fruit production might be pursued by adopting high sowing density and the search for longer-day genotypes.